Double Standards in Financial Reporting as a Form of Tax Avoidance: Perspective of Financial Report Makers - Nurul Wahida; Tenriwaru Tenriwaru; Ratna Sari (SIMAK, 2024)
The phenomenon of tax avoidance which is widespread among taxpayers is considered to be very detrimental to the country. One way for taxpayers to avoid tax is by submitting financial reports that are not true, in other words, taxpayers have at least two financial reports, one of which is the tax version of the financial report. This research was conducted with the aim of finding out how double standards in financial reporting can be a form of tax avoidance. This research uses a qualitative research method with a case study approach. The research results show that double standards in financial reporting are carried out by taxpayers with the aim of tax avoidance. Taxpayers intentionally create at least two different financial reports. One of these reports is used as the basis for taxation in the Annual Corporate Tax Return. Several things that motivate taxpayers to do this include: reluctance to pay taxes, company capital that has not been returned, and avoiding tax audits. The strategy used to implement double standards is by recognizing fictitious expenses, non-deductible expenses, overstated expenses, and not recognizing income. All of these actions are included in tax evasion. When linked to the fraud hexagon theory, these six elements (pressure, opportunity, ability, ego, rationalization and collusion) can influence someone to commit financial statement fraud.